Cellular Phone Has Opened a New Horizon of Socio- Economic Development: A Case Study Of Banglades (International Journal of Engineering and Computer Science, 2017)
Now a day use of cellular phone has become a part of human life. It has a great contribution to make the life modern. Not only on human life cellular phone has a large impacts on socio economic development. As a developing country Bangladesh can not ignore the contribution of cellular phone to it’s continuous development. In this paper , the objective is to find the impact of cellular phone on every part of development in case of Bangladesh. For this purpose this paper has given its attention on agriculture, employment opportunity, banking system, social networking, admission process, entertainment and government revenue of Bangladesh